A novel CRISPR-engineered prostate cancer cell line defines the AR-V transcriptome and identifies PARP inhibitor sensitivities. Issue 11 (22nd April 2019) - Kounatidou, Evangelia; Nakjang, Sirintra; McCracken, Stuart R C; Dehm, Scott M; Robson, Craig N; Jones, Dominic; Gaughan, Luke
Abstract: Resistance to androgen receptor (AR)-targeted therapies in prostate cancer (PC) is a major clinical problem. A key mechanism of treatment resistance in advanced PC is the generation of alternatively spliced forms of the AR termed AR variants (AR-Vs) that are refractory to targeted agents and drive tumour progression. Our understanding of how AR-Vs function is limited due to difficulties in distinguishing their discriminate activities from full-length AR (FL-AR). Here we report the development of a novel CRISPR-derived cell line which is a derivative of CWR22Rv1 cells, called CWR22Rv1-AR-EK, that has lost expression of FL-AR, but retains all endogenous AR-Vs. From this, we show that AR-Vs act unhindered by loss of FL-AR to drive cell growth and expression of androgenic genes. Global transcriptomics demonstrate that AR-Vs drive expression of a cohort of DNA damage response genes and depletion of AR-Vs sensitises cells to ionising radiation. Moreover, we demonstrate that AR-Vs interact with PARP1 and PARP2 and are dependent upon their catalytic function for transcriptional activation. Importantly, PARP blockade compromises expression of AR-V-target genes and reduces growth of CRPC cell lines suggesting a synthetic lethality relationship between AR-Vs and PARP, advocating the use of PARP inhibitors in AR-V positive PC.